PENGARUH MODEL PBL TERHADAP KETERAMPILAN BERPIKIR KRITIS SISWA PADA MATERI PENERAPAN NILAI-NILAI PANCASILA KELAS 6 DI UPTD SDI OETETE 2 - Oktafiani Ingrita Mesak; Maxsel Koro; Kurniayu T. R. A. Ratu (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study is motivated by the limited number of studies addressing the low critical thinking skills among elementary school students, even though this skill has a significant impact on the quality of learning and students’ readiness to face 21st- century challenges. The aim of this research is to examine the effect of applying the Problem-Based Learning (PBL) model on the improvement of critical thinking skills among sixth-grade students in the Civics Education (PPKn) subject at SD Inpres Oetete 2, Kota Kupang. The research employed a quantitative approach with a pre-experimental design, specifically the one-group pretest-posttest model. The sample consisted of 30 sixth-grade students selected through total sampling. Data were collected using a critical thinking skills test and analyzed using a paired sample t-test with the assistance of SPSS software. The findings indicate a significant increase in students’ critical thinking scores after the implementation of the PBL model, with a significance value (2-tailed) of 0.000 < 0.05. These results support constructivist theory, which emphasizes the importance of active student engagement in meaningful learning. The main conclusion is that the PBL model is effective in improving students' critical thinking skills through problem-solving- based learning. The implications of this study include theoretical contributions by enriching the literature on innovative learning strategies at the elementary level, as well as practical recommendations for teachers to integrate PBL into Civics